CONCEPT FORMATION OF ENTERPRISE SUSTAINABLE DEVELOPMENT - R. I. Barmutsky (Наука и техника)
The paper studies a problem of enterprise sustainable development which exists in the context of modern social and economic and dynamic development of the economy in theRepublicofBelarus.The executed analysis of critical situations considers a crisis that makes harmful effects in the whole world and in the economy of theRepublicofBelarusnot only as a negative phenomena but also as a positive element that serves as a stimulator for a new phase of life.The paper examines main stages of transfer to stable sustainable operation of an enterprise that continues its development within the framework of industrial technologies and application of innovation technologies.New information and economic structure is characterized by fast obsolescence of capital and also by certain financial losses for risk, innovations, higher quality of products and execution of service. However even having such economic situation the lost opportunity due to nonuse of the possibility to start change-over to products of new generation covers minimization of expenses achieved at the cost of efficient usage of obsolete technologies and worn-out equipment.